The Value of Record Keeping: a Case Study from Four Elderly Orchid Accessions - Fowler, Andrea (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2005)
The history of four orchids growing at the Royal Botanic Garden Edinburgh (RBGE), some of the oldest accessions still in cultivation in the Indoor Department, is outlined. Records from the time of their arrival have been invaluable in providing an insight into the history of plant collecting, introduction and cultivation methods from the 1890s. They demonstrate the importance of accurate record keeping and the potential for species conservation in botanic gardens.